Effects of Pain-Reporting Education Program on Children's Pain Reports—Results From a Randomized Controlled Post-operative Pediatric Pain Trial - Zontag, Dafna; Honigman, Liat; Kuperman, Pora; Treister, Roi (Frontiers in Pediatrics, 2021)
Objective: Accurate assessment of patients’ pain is an essential part of adequate analgesic treatment. Although reporting pain is a complex task, limited-to-no instructions are provided to pediatric patients regarding this process. Our goal in this randomized parallel-group clinical trial (Clinicaltrial.gov study protocol number NCT04306679) was to evaluate if a training program designed to improve children's ability to understand and use pain scales in a post-surgical setting would affect their pain scores. Methods: Eligible children (aged 8-17), hospitalized for elective surgery and their parents were randomized into two groups. Pre-surgery the intervention group underwent a multi-media program aimed to teach and train how to report pain. The control group received standard pre-surgical instructions. Post-surgery, the children reported their pain on 4 pain scales. The primary outcome was the concordance between children's pain intensity scores reported on four pain scales, both in terms of within-child standard deviation and absolute difference. Results: Ninety-six children met inclusion criteria and completed the study. The trained subjects’ pain reports had significantly (p=0.002) lower within-subject standard deviation (0.41±0.31) than the control group (0.67±0.46). In line, regarding absolute difference, the concordance of children's pain reports was twice better in the trained group (mean difference of 0.43 ± 0.40) than in the control group (0.88 ± 0.70) (p <0.001). Discussion: Our results suggests that children's ability to report pain is a skill that can be improved. Future studies should test the potential clinical impacts of educational interventions aimed to improve pain assessment in children and adults.